2020
DOI: 10.1101/2020.06.05.135913
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frequent loss-of-heterozygosity in CRISPR-Cas9-edited early human embryos

Abstract: CRISPR-Cas9 genome editing is a promising technique for clinical applications, such as the correction of disease-associated alleles in somatic cells. The use of this approach has also been discussed in the context of heritable editing of the human germline. However, studies assessing gene correction in early human embryos report low efficiency of mutation repair, high rates of mosaicism and the possibility of unintended editing outcomes that may have pathologic consequences. We developed computational pipeline… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…We present a case of an unanticipated phenotype associated with CRISPR-Cas9 gene editing. We have previously reported the reinsertion of a deleted fragment close to the CRISPR target site in a mouse line (Summers et al, 2019b) and others have presented similar outcomes in edited human embryos, including loss of whole chromosomes (Alanis-Lobato et al, 2020; Liang et al, 2020; Zuccaro et al, 2020). It is not clear whether the phenotype in these piglets was due to an on-target event similar to these or an off-target event (although this was predicted to have a low probability by the guide design software), perhaps affecting the nearby GLDN gene, as we did not subject the DNA to whole genome sequencing.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…We present a case of an unanticipated phenotype associated with CRISPR-Cas9 gene editing. We have previously reported the reinsertion of a deleted fragment close to the CRISPR target site in a mouse line (Summers et al, 2019b) and others have presented similar outcomes in edited human embryos, including loss of whole chromosomes (Alanis-Lobato et al, 2020; Liang et al, 2020; Zuccaro et al, 2020). It is not clear whether the phenotype in these piglets was due to an on-target event similar to these or an off-target event (although this was predicted to have a low probability by the guide design software), perhaps affecting the nearby GLDN gene, as we did not subject the DNA to whole genome sequencing.…”
Section: Resultsmentioning
confidence: 73%
“…Hydrops was recently seen in an infant with biallelic mutations in the gliomedin gene, GLDN , located 3 megabases downstream of FBN1 (Australian Genomics Health Alliance Acute Care Flagship, 2020; see Table 1 ). There have been a number of reports of DNA changes in the vicinity of a target sequence associated with the use of CRISPR-Cas9 gene editing (Summers et al, 2019; Alanis-Lobato et al, 2020; Liang et al, 2020; Zuccaro et al, 2020). It is possible that GLDN was mutated by the CRISPR-Cas9 process and is responsible for the hydrops fetalis phenotype in our piglets.…”
Section: Discussionmentioning
confidence: 99%
“…A clear and accurate understanding of the global policy landscape for heritable human genome editing is especially important in light of several recent developments, including the He Jiankui debacle 33 ; reports of other researchers stating that they intend to conduct clinical experiments aimed at producing genomeedited children 34 ; ongoing debate about the need for a global moratorium 32,[35][36][37] ; growing public and policymaker interest in, and concerns about, such experiments 38,39 ; recently published policy considerations on human genome editing 36,[40][41][42] ; advances in genome editing in human embryos, which confirm significant safety concerns [43][44][45][46] ; the recent report Heritable Human 47 To promote clarity and accuracy, this survey provides an overview of the existing global policy landscape for both heritable genome editing and germline genome editing-two related research practices with differing aims and consequences. Heritable genome editing involves the transfer of genetically modified embryos to a uterus to initiate a pregnancy that would result in the birth of a child with a modified genome.…”
Section: Introductionmentioning
confidence: 99%
“…As a precaution, Alanis-Lobato et al [ 65 ] from the Francis Crick Institute have just reported a computational pipeline for single-cell genomics and transcriptomics of OCT4 ( POU5F1 ) CRISPR/Cas9-targeted and Cas9-only control human preimplantation embryos that allowed them to evaluate hard-to-detect on-target mutations. They observed loss-of-heterozygosity, segmental loss and gain of chromosomes, as well as unintended genome editing in analysed human embryo cells.…”
Section: Crispr/cas9 System and Tp53 Pathway Gementioning
confidence: 99%